Automation of the Feeding System for Washing Vehicles Using Low Cost Devices - Saá, Fernando (2020)
Vehicle washing is a profitable business today, but it produces unwanted environmental effects that should be considered; autonomous systems are a viable solution for the optimization of resources in production processes and services. This paper presents the implementation of an automatic resource feeding system for vehicle washing using low cost devices. The system consists of an Arduino Mega controller, ultrasonic sensors to measure the level of liquids, several actuators, Bluetooth communication devices and a mobile application. The results present the consumption of resources in a month of operation, demonstrating the benefits of this proposal. © 2020, Springer Nature Switzerland AG.